Modificações superficiais de aço Ti-UBC por processos a plasma em configuração triodo: influência no comportamento ao desgaste e à corrosão - Carlos Alberto Llanes Leyva (2011)
Ultra-low carbon (ULC) steels exhibit low yield strength and excellent formability. Plasma Assisted Physical Vapor Deposition (PAPVD) could be a coating method for enhancing mechanical, corrosion and wear resistances of low strength materials (MATTHEWS, 1995). However, when deposited onto low mechanical resistance alloys PAPVD coatings may undergo premature failure if the substrate plastically deforms under heavy load. Extra load support is usually required for hard coatings to perform satisfactorily. Combined treatments involving plasma nitriding and PAPVD coating have been used to improve the load-bearing capacity of hard films (AVELARBATISTA, 2005; MANCOSU, 2005; SANTOS, 2009). Present work focuses the characterization, corrosion behavior and micro abrasive wear resistance of Ti-stabilized Ultra-Low Carbon (ULC) steel after surface modification by D.C Triode Plasma Nitriding (DC-TPN) and sequential coating with Cr-Al-N by Electron Beam Plasma Assisted Physical Vapor Deposition (EB-PAPVD). Manufacturing processes are described. The ULC steel substrate, the nitrided steel and the corresponding Cr-Al-N duplex were studied. Results from corrosion tests of plasma-modified systems were compared to those from uncoated, electro-galvanized and galvannealed ULC steel sheets. Open Circuit Potential (OCP) tests were performed. The corrosion properties were evaluated via electrochemical potentiodynamic tests in aerated chloride-containing solution (3.5% NaCl). Polarization curves were investigated from -2.5 V to +1.5 V, beyond the pitting potential for Cr-Al-N coatings which lies between 0.6 V and 0.8 V depending on the Al/Cr ratio (DING, 2008). Corrosion parameters were measured and compared: EOCP (V); Icorr; (A/cm2); Ecorr (V); Rp (W*cm2) and relative efficiency of protection against corrosion _c (%). SEM post-corrosion studies were conducted and the corrosion modes - from general corrosion in uncoated steel to pitting in coated systems are discussed. Characterization of chemical composition, microstructure, phases, and surface roughness were conducted. Coating thickness for the coated systems was measured by calotest based on the inner and outer diameter of the wear scars. Under the experimental conditions of the present study, the results for corrosion resistance could be correlated to the differences in morphology and composition of the surfaces. For example, galvannealed samples showed Zn-Fe phases _ _ - _ - _1 - _- aFe varying from surface to substrate, while the duplex system goes from cfc-Cr-Al-N coating on top of a g´-Fe4N nitrided layer to an aFe substrate with N in solid solution. Results indicate that it is feasible to manufacture duplex Ti-ULC steel via DC-TPN and EB-PAPVD with actual improvement of the corrosion resistance. Potentiodynamic curves clearly showed a shift to higher corrosion potentials and lower corrosion current intensity from the untreated ULC substrate to the duplex system. The micro-abrasive wear behavior was also studied for the different systems under investigation. Micro-abrasive wear tests were performed in fixed-ball configuration up to 1350 revolutions using SiC abrasive slurry and a 25mm diameter AISI 52100 steel ball. Additional characterization was performed via micro-hardness and instrumented indentation hardness measurements, as well as stylus profilometry on both initial and worn surfaces of the samples. SEM and EDS analyses were conducted over the worn samples; the micro-abrasion mechanisms are presented and discussed. Nitrided steel and duplex system were, respectively, 2.5 and 3.4 times harder than the untreated Ti-ULC steel. The wear coefficient of nitrided steel was 36 % lower than that of the parent Ti- ULC steel. Regression analyses were used to calculate substrate (ks) and coating (kc) wear coefficients for the duplex system, the latter being 6.6 times lower than that of the nitrided steel. Results indicate that it is feasible to manufacture duplex Ti-ULC steel via PAPVD, as significant improvements in wear resistance were recorded for both nitrided and duplex-treated steels. Duplex treatment clearly was the most effective method to enhance the wear resistance of ULC steels. These results suggest a wider range for applicability of the ULC steels, where high drawability and high superficial mechanical resistance may be necessary